Implementasi Nilai-Nilai Karakter Religius Siswi SMP Negeri 2 Gunung Jati Melalui Kegiatan Keputrian - Syafira, Agis Sholikhatu; Alirahman, Agus Dian; Hanafi, Akhmad (Permata : Jurnal Pendidikan Agama Islam, 2024)
This research focuses on how the students of SMP Negeri 2 Gunung Jati apply religious character values in the activities of princesses. The context of this research is the role of schools in shaping the religious character of female students. Middle school students are very vulnerable to environmental influences, especially in terms of character growth and spiritual values. Therefore, it is important for junior high school students to implement religious character values through princess activities. This will help them develop an Islamic identity, strong morals and good character qualities.This research aims to explain how schoolgirls apply religious character values in daily life, both at school and at home, through princess activities.This research was conducted using narrative qualitative method. The data were collected through observation, interviews, and documentation. This research collected data through observation of women in prayer rooms or classrooms and in-depth interviews with female supervisors. This research uses the techniques of collecting, reducing, presenting, and drawing conclusions.The results revealed that students of SMP Negeri 2 Gunung Jati can apply religious character values through princess activities. This princess activity has fostered students to have good morals, discipline, school rules, respect for teachers and parents. With the help of female teachers and principals, students can apply these values. Keywords: Implementing; Character Values; Religious Character